Modeling of a Computer Using the Norton Model for Harmonic Analysis - Arismendy-Mira, Julián Esteban; Henao-Muñoz, Andrés Camilo; Saavedra-Montes, Andrés Julián (Scientia et Technica, 2018)
The Norton model of a personal computer for harmonic analysis is presented in this paper. The parameters of the model are estimated from two experiments, in which the computer is powered by two different voltages. The model is simulated and the current and voltage waveforms are compared with the experimental waves. The results show that Norton model is valid to represent a personal computer because the error index of the current and voltage waveforms and harmonic spectrums is lower than 8.5%.